Hubungan Asupan Natrium dan Status Gizi Terhadap Tingkat Hipertensi Pada Pasien Rawat Jalan Di RSUD Kota Makassar - Hasbullah Darmawan; Abdullah Tamrin; Nadimin Nadimin (Jurusan Gizi Poltekkes Kemenkes Makassar, 2018)
Hypertension is a big problem, not only in western countries but also in Indonesia. Every year hypertension or high blood pressure contributes to the deaths of nearly 9.4 million people due to heart disease and stroke and if combined these two diseases are the number one cause in the world.This study aims to analyze the relationship between sodium intake and nutritional status to the level of hypertension in outpatients in RSUD Makassar City. This study used cross sectional study design. The sample is outpatient of RSUD Makassar City. Data of sodium intake and nutritional status were obtained by recall 1x24 hours and anthropometry measurement, while blood pressure data were obtained from patient rekammedic data. The results showed that samples with normal sodium intake tended to have mild hypertension that was 12 people (85,7%) while sample with sodium intake was more likely to have moderate hypertension that is 12 people (75%). Samples of normal nutritional status with mild hypertension tends to be 12 people (80%) while the sample with abnormal nutritional status tend to have moderate hypertension is 11 people (73,3%). The relationship between sodium intake and nutritional status to hypertension level. It is recommended to hospital nutritionists to provide further consultation on low-salt diet as well as improved nutritional status. In addition there is also a further understanding of hypertensive patients about the cause of hypertension to be more vigilant against hypertension disease.